Impact of exercise on drug cravings: mediating role of cardiorespiratory fitness and inhibitory control - Li, Boya; Zhou, Yuehui; Qian, Youling; Wu, Juhua (Frontiers in Psychology, 2025)
BackgroundContemporary research has consistently demonstrated a link between physical exercise, inhibition, and drug cravings, with several hypotheses proposed to explain how exercise enhances inhibition. However, few studies have explored the mechanisms underlying this effect. This study investigates the pivotal role of cardiorespiratory fitness in mediating the impact of physical exercise on inhibition and drug cravings.MethodsIn this study, the researchers selected participants who had completed physical detoxification in China’s compulsory isolation drug rehabilitation centers. Moreover, we conducted surveys and assessed cardiorespiratory fitness using tools such as the Physical Exercise Rating Scale, Inhibition Scale, Drug Craving Scale, and Queen College Step Test. Additionally, we employed exploratory and confirmatory factor analyses, correlation analysis, regression analysis, and structural equation model (SEM) to analyze the study’s data.Results and findingsThe findings of this study reveal that physical exercise significantly reduces drug craving by improving cardiorespiratory fitness and enhancing inhibition. Furthermore, it showed that men had better physical exercise levels, cardiorespiratory fitness, and inhibition compared to women, while women exhibited higher psychological cravings. Besides, the study also highlighted that longer years of drug use were associated with lower physical exercise, reduced cardiorespiratory fitness, and weaker inhibition, leading to higher drug cravings. In addition, cardiorespiratory fitness and inhibition acted as mediators between physical exercise and drug craving, with the combination of both factors serving as a chain mediator in reducing cravings. These findings suggest that physical exercise, particularly through improving cardiorespiratory fitness, plays a key role in mitigating drug cravings and supporting rehabilitation efforts for drug dependence.